2003
DOI: 10.1080/0144361031000074728
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal intrauterine fetal death: a prospective study in a tertiary hospital in south-western Saudi Arabia

Abstract: This study was conducted to determine the frequency of antenatal intrauterine fetal death (IUFD) and the associated maternal and fetal risk factors in women who presented at a regional tertiary hospital in Saudi Arabia. Over a 5-year period, 191 consecutive cases of IUFD presented and were studied prospectively. Relevant maternal and fetal data were obtained. The stillbirth rate during the period was 10 per 1000 deliveries. In 41% of the cases, the associated causal factors could not be determined. There was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 13 publications
0
23
2
1
Order By: Relevance
“…7,8 In our study diabetes was found to be associated in 1.35% cases which was in contrast to study conducted by Gunton where diabetes came out to be the major factor for IUD. 9 A past history of intrauterine fetal death indicates some subclinical genetic or chromosomal problem which can recur in future pregnancies.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…7,8 In our study diabetes was found to be associated in 1.35% cases which was in contrast to study conducted by Gunton where diabetes came out to be the major factor for IUD. 9 A past history of intrauterine fetal death indicates some subclinical genetic or chromosomal problem which can recur in future pregnancies.…”
Section: Discussioncontrasting
confidence: 55%
“…4 The critical peak at which fetuses were lost is variable in theliterature. 7,8,10,14 This may indicate that predisposing pathology for IUFD is different in different communities.…”
Section: Discussionmentioning
confidence: 99%
“…A study of AFD in Saudi Arabia [12]. Observed that grand-multiparous women rarely access prenatal services as they feel over-confi dent about their knowledge of pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in some countries SB has been defi ned based on births occurring ≥ 20 weeks of gestation, using the number of singleton deliveries only as the denominator or by using a minimum weight of 500grammes [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation